1968
DOI: 10.1111/j.1476-5381.1968.tb08479.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the chemoreceptor trigger zone in histamine‐induced emesis

Abstract: . In unanaesthetized dogs, the emetic action of histamine was studied after its injection into the cerebral venricles through chronically implanted cannulae in order to elucidate the role of the chemoreceptor trigger zone (CT‐zone), situated in the area postrema, for this emesis. . On injection into the lateral cerebral ventricle, about 10 times larger doses of histamine (3 mg) were required regularly to produce emesis, and it occurred after a longer latency than on injection into the fourth ventricle. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…We believe that morphine induces emesis by an action on the enkephalin receptors in the emetic trigger zone and apomorphine may be acting on dopamine receptors in the CTZ. There is already evidence in support of histamine receptors in the chemoreceptor trigger zone (Bhargava & Dixit, 1968;Bhargava, Dixit & Palit, 1976). Thus, there may be a variety of receptors in the CTZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that morphine induces emesis by an action on the enkephalin receptors in the emetic trigger zone and apomorphine may be acting on dopamine receptors in the CTZ. There is already evidence in support of histamine receptors in the chemoreceptor trigger zone (Bhargava & Dixit, 1968;Bhargava, Dixit & Palit, 1976). Thus, there may be a variety of receptors in the CTZ.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic implantation of a metal cannula into either a lateral cerebral ventricle or into the IVth ventricle was performed aseptically under pentobarbitone sodium anaesthesia, according to the method described by Bhargava & Dixit (1968). The correct placement of cannula was ascertained by withdrawal of clear cerebrospinal fluid from the cannula, by a postive emetic response to an injection of apomorphine into the cannulated lateral (2 jg) or IVth ventricle (0.5 jig) 3 to 4 days after the implantation and, finally, on autopsy.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been proposed that histamine receptors in the ECT zone of the area postrema of the dog may fully account for the emesis induced by intraventricular histamine (Bhargava & Dixit, 1968), the nature of these receptors was not known. The present study has clearly shown the importance of both H1-and H2-receptors in the emetic action of centrally administered histamine.…”
Section: Discussionmentioning
confidence: 99%
“…The area postrema is very rich in biogenic amines, including histamine (Adam, 1961) but their precise role in the emetic chemoreceptor trigger (ECT) zone is not known. However, intraventricular administration of histamine in dogs elicited emesis which was completely blocked after surgical ablation of the ECT zone (Bhargava & Dixit, 1968 …”
Section: Introductionmentioning
confidence: 99%
“…Dopa mine and L-dopa [Lotti and Clark, 1974], histamine [Bhargava and Dixit, 1968] and metenkephalin [Bhargava et al, 1981] are among these putative candidates. Experi ments are needed to track concentrations of these elements and others in the CSF during the motion sickness process.…”
Section: Discussionmentioning
confidence: 99%